2021
DOI: 10.3390/jcm10010144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Skin Lesions by Using Single-Step Multiframe Detector

Abstract: An artificial intelligence algorithm to detect mycosis fungoides (MF), psoriasis (PSO), and atopic dermatitis (AD) is demonstrated. Results showed that 10 s was consumed by the single shot multibox detector (SSD) model to analyze 292 test images, among which 273 images were correctly detected. Verification of ground truth samples of this research come from pathological tissue slices and OCT analysis. The SSD diagnosis accuracy rate was 93%. The sensitivity values of the SSD model in diagnosing the skin lesions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…However, these techniques are not yet commercially available; flow cytometry and TCR-gene clonality assessment are currently the only routinely available diagnostics for peripheral blood. Other tools include reflectance confocal microscopy, allowing non-invasive visualization of characteristic MF skin morphology [60,61], and artificial intelligence algorithms based on clinical images and histopathology [62,63]. However, their place in the diagnostic process for MF remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, these techniques are not yet commercially available; flow cytometry and TCR-gene clonality assessment are currently the only routinely available diagnostics for peripheral blood. Other tools include reflectance confocal microscopy, allowing non-invasive visualization of characteristic MF skin morphology [60,61], and artificial intelligence algorithms based on clinical images and histopathology [62,63]. However, their place in the diagnostic process for MF remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…SSD is one of the best AI models in image identi cation and location, which consist of at least 16 layers 31,32 . It is an effective object detector for multiple targets recognition within just one stage 10 . Yao-Kuang et al 31 used a SSD system for diagnosing esophageal cancer, which showed good diagnostic performance and the accuracy can achieve 90%.…”
Section: Discussionmentioning
confidence: 99%
“…AI refers to a serious of technologies that allow computers and machines to imitate human intelligence 8 . It has come to play an important role in healthcare, including analyzing a diverse array of patient data and simulating human logic to perform some tasks [9][10][11][12] . AI iteratively learn the intrinsic statistics underlying the pairing data and algorithm, to make plan on unseen data 8,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by using hyperspectral imaging technology combined with artificial intelligence deep learning methods to perform spectral data for esophageal cancer will offer a faster and more accurate diagnosis. The hyperspectral images have nanometer-level spectral intervals and hence the amount of spectrum information that can be detected is much larger than that of multispectral images [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The image spectrum conversion is the use of an imaging spectrometer to obtain an image that has a wide wavelength measurement range, the image is divided into a multispectral image and a hyperspectral image according to the spectral resolution.…”
Section: Introductionmentioning
confidence: 99%